Obrazy miasta w Pozwól rzece płynąć Michała Cichego. Prolegomena - Maroszczuk, Grażyna (Tematy i Konteksty, 2018)
Michał Cichy is the author of two books Always is today and Let the river flow.The subject of literary reflection of the writer is modern, transient, heterotopic city. Sketch of Grażyna Maroszczuk presents reflections on the literary updating of the city in the metaphor of the “walking book” of peripatetic, observer and resident of Warsaw’s old district of Ochota.